Phytochemical screening and antioxidant activity of crude plant extracts from apium graveolens (celery) plant - Maisarah Zawawi (2024)
Apium graveolens is a biennial plant of the Apiaceous family. This study aims to clarify its importance and reveal its phytochemical profile, which is comprised of several substances such as terpenoids, flavonoids, steroids, and saponins. This study also employs the maceration technique to extract these phytochemicals to compare the effectiveness of two solvents which are 56.7% ethanol and 100% distilled water. Furthermore, the antioxidant capacity of the Apium graveolens extracts was accessed through the utilization of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay technique. The predicted bioactive component was present in the plant extract, according to the findings of the phytochemical screening. 56.7% ethanol extracts gave positive results for steroids and flavonoids but absent for saponins and terpenoids. Every phytochemical test that was conducted on distilled water extracts had positive results. Next, DPPH radical inhibition and IC₅₀ data show that plant extract has better antioxidant activity than ascorbic acid. A significant antioxidant activity is shown by the distilled water extract's value of 1.171 mg/mL, which is followed by the ascorbic acid value of 0.766 mg/mL and the ethanol extract of 0.786 mg/mL.